(untitled) (Research, Society and Development, 2020)
Canine Visceral Leishmaniasis (CVL) is a chronic zoonosis whose etiologic agent is Leishmania chagasi transmitted by Lutzomyia insects. It is a systemic disease affecting lymphoid organs (bone marrow, spleen and lymph nodes) distributed throughout the body. The spread of the disease is closely related to the ways in which health professionals approach it. However, it is very important that they have full knowledge and mastery over the disease. Therefore, the objective of this work is to evaluate the knowledge about CVL of veterinarians working in Mineiros/GO city and what has been done by them to face real cases of the disease. Ten interviews were carried out through semi-structured questionnaires containing 12 questions. All respondents knew the CVL, and related the form of transmission through the straw mosquito. When asked about animals that could be infected, 60% answered dogs and cats and 40% only dogs. Only one respondent presented a complete answer about the symptoms of the affected animals. There was a high level of knowledge in relation to diagnosis and treatment. Regarding preventive methods, 33.3% related the use of repellent collar, 22.22% local hygiene, 27.8% animal vaccination, 5.55% repellents, 5.55% avoiding insect bites and finally, 5. 55% included euthanizing the infected dog. However, 90% of professionals recommend vaccination. It is concluded that the professionals working in Mineiros/GO have high knowledge about this disease, mainly regarding the transmission mode, diagnoses and preventive measures. However, there is a lack of knowledge regarding the symptoms presented by infected dogs.